Effect of weather on temporal pain patterns in patients with temporomandibular disorders and migraine. (30th March 2017) - Cioffi, I.; Farella, M.; Chiodini, P.; Ammendola, L.; Capuozzo, R.; Klain, C.; Vollaro, S.; Michelotti, A.
Summary: Patients with masticatory muscle pain and migraine typically report that the intensity of pain fluctuates over time and is affected by weather changes. Weather variables, such as ambient temperature and humidity, may vary significantly depending on whether the individual is outdoor or indoor. It is, therefore, important to assess these variables at the individual level using portable monitors, during everyday life. This study aimed to determine and compare the temporal patterns of pain in individuals affected with facial and head pain and to investigate its relation with weather changes. Eleven patients (27·3 ± 7·4 years) with chronic masticatory muscle pain (MP) and twenty (33·1 ± 8·7 years) with migraine headache (MH) were asked to report their current pain level on a visual analogue scale (VAS) every hour over fourteen consecutive days. The VAS scores were collected using portable data‐loggers, which were also used to record temperature, atmospheric pressure and relative humidity. VAS scores varied markedly over time in both groups. Pain VAS scores fluctuate less in the MP group than in the MH group, but their mean, minimum and maximum values were higher than those of migraine patients (all P < 0·05). Pain scores <2 cm were more common in the MH than in the MP group ( P < 0·001). Perceived intensity of pain was negatively associated with atmospheric pressure in the MP group and positively associated with temperature and atmospheric in the MH group. Our results reveal that patients with masticatory muscle pain and patients with migraine present typical temporal pain patterns that are influenced in a different way by weather changes.